Pengambilan Keputusan dalam Budidaya Tembakau: Studi Fenomenologi pada Komunitas Petani di Temanggung - Luluk Dewi Handayani (Fakultas Psikologi Universitas Sanata Dharma, 2021)
This qualitative research aims to explore the dynamics of farmers' decision making in choosing tobacco as a cultivated crop. Data analysis is done using the Interpretative Phenomenological Analysis (IPA) method, using several stages of analysis that include: (1) Reading and re-reading, (2) Initial noting, (3) Developing emergent themes, (4) Searching for connection across emergent themes, (5) Moving to the next case, (6) Looking for patterns across cases. Data collection was conducted by semi-structured interview techniques with three tobacco farmers in Bansari Subdistrict, Temanggung Regency. The selection of informants was carried out using snowball techniques. The study found that farmers' decisions to grow tobacco were shaped by their social environmental factors through social interactions that occurred, also the consciousness state of the tobacco’s farmer in making decision.